The Inquiry Commissions and the Differences between the Tineo Cabrera & Toledo’s Judgments - Landa Arroyo, César (2015)
The present article addresses the issue about the differences between the Tineo Cabrera and Toledo´s precedents, which is about the clarifications made by the Constitutional Court concerning the fundamentals rights like prior and detailed notification and lifting banking secrecy made in assembly parliamentary. Likewise, give its opinion about the inquiry commissions performance and the improvements that must be implement to its objective actuation and non-arbitrary.